Use of rumination and activity data as health status and performance indicators in beef cattle during the early fattening period. (January 2018) - Marchesini, Giorgio; Mottaran, Davide; Contiero, Barbara; Schiavon, Eliana; Segato, Severino; Garbin, Elisabetta; Tenti, Sandro; Andrighetto, Igino
Highlights: Patterns of activity and rumination in beef cattle allow the detection of BRD and lameness. Patterns of activity and rumination in beef cattle help in predicting average daily weight gain. The use of individual sensors help in early diagnosis of cattle diseases, facilitating early and targeted therapies. Abstract: The aim of this study was to measure the level of activity and rumination in young bulls and to assess whether these data can be used as indicators of health status and average daily weight gain (ADG). Two groups of animals (period 1: n = 108 animals; period 2: n = 106 animals) were fitted with sensors to measure daily activity and rumination, were weighed on arrival and at the end of the trial (70 days) and were checked twice daily to verify their health condition. Any clinical signs and therapies were recorded. The dishomogeneity index of rumination (DR), and the daily dishomogeneity indices of activity (DDA) and rumination (DDR), were calculated. Bulls had an ADG of 1.42 ± 0.38 kg/day and showed an average duration of daily rumination of 404 ± 63 min and an average activity of 474 ± 46 bits, respectively. Animals characterised by low ADG had lower values of minimum daily rumination ( P = 0.01) and DDA ( P < 0.001), and a greater rumination range ( P = 0.007) and DR ( P = 0.003). Bovine respiratory disease and lameness were detected 31 and five times, respectively; among affected animals, the average daily activity, rumination and DDA were lower ( P < 0.05) at 3–6 days before the onset of visible clinical signs, whereas DDR increased compared to the values when individuals were apparently healthy. The use of individual sensors appears promising for the early diagnosis of disease in beef cattle and for improving herd management.